(untitled) (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: This study investigates whether participants of the Flemish programme Physical Activity on Referral (PAR) maintain increased physical activity levels after the coaching ends, focusing on long-term behavioural changes and changes in psychosocial determinants of physical activity. Methods: An online survey was conducted among former PAR participants, distributed by PAR coaches. Responses from 94 respondents were analysed. The survey included questions about physical activity levels and psychosocial determinants ( e.g. motivation, barriers, and self-efficacy) before the start of PAR (pre), at the end of the coaching (post), and at the time of the survey (follow-up). Participants self-reported their activity levels and experiences. Guidance of the PAR trajectory varied based on need for support, up to a maximum of 14 hours of individual coaching spread over two years. All participants received the questionnaire simultaneously and had completed the coaching at least three months to over two years ago. Results: The survey revealed that 63.8% of respondents reported higher physical activity levels at follow-up compared to before the programme, while 24.5% maintained the same level of activity. A notable finding was that a significant number of participants increased their activity levels even after the coaching ended. The study found no significant differences in the change in physical activity levels from pre to follow-up based on gender, educational level, or age group. At follow-up the respondents had less barriers to be physically active compared to pre. Among the group that is more physically active from pre to follow-up, the following psychosocial determinants improved: autonomous motivation increased, controlled motivation decreased, social support increased, and self-efficacy increased. Conclusions: The PAR programme seems to contribute to sustainable behavioural changes in physical activity. These findings suggest that the coaching methods used in PAR can lead to long-term increases in physical activity. Limitations of this study include self-reporting of physical activity from a long time ago (recall bias) and the absence of a control group. Support/Funding Source: This study was conducted in collaboration with master students of UGent and supported by the Fleming Institute of Healthy Living. No additional funding was in place